1983
DOI: 10.1083/jcb.97.3.713
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrastructure of a unicellular cyanobacterium.

Abstract: The first complete three-dimensional ultrastructural reconstruction of a cyanobacterium was accomplished with high-voltage electron microscopy and computer-aided assembly of serial sections. The precise arrangement of subcellular features within the cell body was very consistent from one cell to another. Specialized inclusion bodies always occupied specific intracellular locations. The photosynthetic thylakoid membranes entirely surrounded the central portion of the cytoplasm, thereby compartmentalizing it fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 57 publications
5
47
0
Order By: Relevance
“…It was suggested that, during the transition of proplastids to chloroplasts, thylakoid membranes originate from invaginations of the inner envelope in algal chloroplasts or proplastids of vascular plants, while in mature chloroplasts, the membrane system is maintained by vesicle transport (Rast et al, 2015). Contact points of thylakoid membranes with the plasma membrane were seen in 3D micrographs of a cyanobacterium (Nierzwicki-Bauer et al, 1983). Evidence to support this model in higher plants has been challenging due to the transient nature of membrane remodeling in plastids (Shimoni et al, 2005).…”
Section: A Model: Ion Homeostasis At Biogenesis Centers For Thylakoidsmentioning
confidence: 95%
“…It was suggested that, during the transition of proplastids to chloroplasts, thylakoid membranes originate from invaginations of the inner envelope in algal chloroplasts or proplastids of vascular plants, while in mature chloroplasts, the membrane system is maintained by vesicle transport (Rast et al, 2015). Contact points of thylakoid membranes with the plasma membrane were seen in 3D micrographs of a cyanobacterium (Nierzwicki-Bauer et al, 1983). Evidence to support this model in higher plants has been challenging due to the transient nature of membrane remodeling in plastids (Shimoni et al, 2005).…”
Section: A Model: Ion Homeostasis At Biogenesis Centers For Thylakoidsmentioning
confidence: 95%
“…Explorations of the ultrastructure of cyanobacterial cells in three dimensions began with computer-aided reconstructions of serial sections of Synechococcus sp. PCC 7002 (formerly Agmenellum quadruplicatum; Nierzwicki-Bauer et al, 1983), and progressed to using advanced techniques such as electron tomography and cryo-electron tomography. Recent analyses of tomographic data collected from #200-nm-thick sections through cyanobacterial cells have shown that thylakoid membranes are connected by junctions and channels linking adjacent membranes in Prochlorococcus strains MIT9313 and MED4 (Ting et al, 2007) and by branching and fusion in Microcoleus sp.…”
mentioning
confidence: 99%
“…The ultrastructure and organization of the membranes is however still under debate and mainly two different opinions prevail concerning the organization of plasma and thylakoid membranes. One is that the two membranes are continuous, making the periplasm and lumen a common compartment, the second that the membranes are completely separated (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Knockout mutations of the two genes, however, give significantly different results: whereas LepB2 appears to be totally essential for cell viability, cells with a deletion in LepB1 are still able to grow under heterotrophic conditions in dim light (26). The light sensitivity disappeared when 3-(3,4-dichlorophenyl)-1,1-dimetylurea (DCMU) 1 was present. DCMU inhibits the reduction of the plastoquinone (PQ) pool by photosystem II (PSII) and this indicates that the primary cause for the photosensitivity observed is the impairment in electron flow downstream of PSII.…”
mentioning
confidence: 99%